2021
DOI: 10.1111/mmi.14702
|View full text |Cite
|
Sign up to set email alerts
|

Widespread bacterial utilization of guanidine as nitrogen source

Abstract: Although guanidine is widely used in the manufacturing of plastics, as reactant in certain explosives and propellants and as a chaotropic reagent in biochemistry, a prominent role in nature has not been identified to date. The lack of knowledge about the physiological role and source of free guanidine in biological systems is in bright contrast to the widespread occurrence of guanidine riboswitches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…55,56 This explains why the majority of hydroxyguanidine is exported and not used by the bacterium for nitrogen assimilation as we have demonstrated recently for guanidine. 24 The homology search of the canavanine-g-lyase revealed that the enzyme is also found in Rhizobiales. We confirmed that the CangL homolog of R. leguminosarum is indeed degrading canavanine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…55,56 This explains why the majority of hydroxyguanidine is exported and not used by the bacterium for nitrogen assimilation as we have demonstrated recently for guanidine. 24 The homology search of the canavanine-g-lyase revealed that the enzyme is also found in Rhizobiales. We confirmed that the CangL homolog of R. leguminosarum is indeed degrading canavanine.…”
Section: Discussionmentioning
confidence: 99%
“…55,56 This explains why the majority of hydroxyguanidine is exported and not used by the bacterium for nitrogen assimilation as we have demonstrated recently for guanidine. 24…”
Section: Discussionmentioning
confidence: 99%
“…These guanidine riboswitches (Gdn) sense Gdm + with high sensitivity and specificity [17] . Derived from the genomic location of the Gdm + ‐sensing riboswitches, Gdm + has then been proposed to play an important role in the detoxification of cells via its carboxylation [13] but also to serve as a source of nitrogen [18] …”
Section: Introductionmentioning
confidence: 99%
“…[17] Derived from the genomic location of the Gdm + -sensing riboswitches, Gdm + has then been proposed to play an important role in the detoxification of cells via its carboxylation [13] but also to serve as a source of nitrogen. [18] To date, four different classes of Gdm + -sensing riboswitches have been discovered termed guanidine-I to guanidine-IV. [15,18,19] Many of these Gdm + -sensing riboswitches are biologically well characterized and structural models of isolated hairpins were reported for all the four riboswitch classes including Gdn-II from Escherichia coli (PDB: 5NDI), from Gloeobacter violaceus (5NOM and 5NDH) and from Pseudomonas aeruginosa (5VJ9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation